2016
DOI: 10.1590/0101-60830000000103
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling in patients with schizophrenia: a systematic review

Abstract: Background: Neuroimaging studies are an invaluable source of information about the physiopathology of schizophrenia. Arterial spin labeling (ASL) is a new magnetic resonance technique (MRI) that is able to effectively evaluate brain function without the use of radiation. Objective: To make a systematic review of studies using ASL to compare resting-state regional cerebral blood flow (rCBF) patterns in patients with schizophrenia and healthy controls. Methods: Original articles were searched for on PubMed, Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Abnormal resting state brain activity has also been reported in a meta-analysis of studies using PET, fMRI and ASL and the authors identified hypoactivation in the ventromedial prefrontal cortex, left hippocampus, posterior cingulate cortex, precuneus, and hyperactivation in bilateral lingual gyrus of schizophrenic patients compared to controls 31 . Lastly, in a systematic review of ASL imaging in schizophrenia, the authors identified convergent reductions in cerebral blood flow in the frontal lobe, left middle frontal gyrus, inferior frontal gyrus, lingual gyrus, cuneus, middle occipital gyrus, fusiform gyrus, anterior cingulate and parietal lobe, with the putamen as the only region showing increased CBF in schizophrenia 32 . The same study also found inconsistent results for middle temporal, parahippocampal, precuneus and thalamic regions 32 .…”
Section: Imaging Brain Function and Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal resting state brain activity has also been reported in a meta-analysis of studies using PET, fMRI and ASL and the authors identified hypoactivation in the ventromedial prefrontal cortex, left hippocampus, posterior cingulate cortex, precuneus, and hyperactivation in bilateral lingual gyrus of schizophrenic patients compared to controls 31 . Lastly, in a systematic review of ASL imaging in schizophrenia, the authors identified convergent reductions in cerebral blood flow in the frontal lobe, left middle frontal gyrus, inferior frontal gyrus, lingual gyrus, cuneus, middle occipital gyrus, fusiform gyrus, anterior cingulate and parietal lobe, with the putamen as the only region showing increased CBF in schizophrenia 32 . The same study also found inconsistent results for middle temporal, parahippocampal, precuneus and thalamic regions 32 .…”
Section: Imaging Brain Function and Perfusionmentioning
confidence: 99%
“…Lastly, in a systematic review of ASL imaging in schizophrenia, the authors identified convergent reductions in cerebral blood flow in the frontal lobe, left middle frontal gyrus, inferior frontal gyrus, lingual gyrus, cuneus, middle occipital gyrus, fusiform gyrus, anterior cingulate and parietal lobe, with the putamen as the only region showing increased CBF in schizophrenia 32 . The same study also found inconsistent results for middle temporal, parahippocampal, precuneus and thalamic regions 32 . Taken together, functional imaging studies point towards altered metabolic or hemodynamic activity in frontal, cingulate, parietal and occipital brain regions with a few areas of hyperactivity, such as the putamen and sensorimotor regions, but more work is needed to determine the clinical implications of these observations.…”
Section: Imaging Brain Function and Perfusionmentioning
confidence: 99%
“…Limitations in the imaging studies on schizophrenia are represented by the issue that most of them mainly recruited chronic patients and individuals taking antipsychotic treatment, therefore making it difficult to identify the time of the brain changes and the effect of the treatment exposure [ 146 , 147 ]. Functional neuroimaging studies have shown alterations in the brain metabolism and the blood flow in the frontal, cingulate, parietal, putamen, and sensorimotor regions [ 148 , 149 , 150 , 151 ]. Dopamine dysfunction has also been observed in schizophrenic patients.…”
Section: Neuroimagingmentioning
confidence: 99%
“…11,13 Pseudo-continuous arterial spin labeling (pCASL) is a noninvasive magnetic resonance (MR) technique that uses arterial water as a diffusible tracer to form CBF images with high spatial resolution. 18 Arterial spin labeling (ASL) studies in schizophrenia are generally small and with some variability in findings (reviewed in Guimarães et al 19 and Théberge 20 ). Nevertheless, frontal hypoperfusion at rest has been reported in several studies, [21][22][23][24][25][26][27] most frequently in the anterior cingulate cortex 21,26,27 and the medial frontal gyrus.…”
Section: Introductionmentioning
confidence: 99%